Polyurea Dendrimer Folate-Targeted Nanodelivery of l-Buthionine sulfoximine as a Tool to Tackle Ovarian Cancer Chemoresistance - Cruz, Adriana (2020)
The research was funded by iNOVA4Health—UID/Multi/04462/, a program financially supported by the Fundação para a Ciência e a Tecnologia—Ministério da Educação e Ciência (FCT-MCTES), through nationalfunds and co-funded by FEDER under the PT2020 Partnership Agreement. We also acknowledge funding from FCT-MCTES through the project DREAM—PTDC/MEC-ONC/29327/2017 and FAI2017 from IPOLFG internal funding.